USING AUDIO VISUAL AIDS IN EFL CLASSES: INFORMATICS STUDENTS’ RESPONSES - Maria Istiqoma; Tutut Nani Prihatmi; Rini Anjarwati (PROJECT (Professional Journal of English Education), 2023)
Numerous researchers state that exciting learning materials and media can help higher education students increase their learning motivation. Therefore, the need to develop technology-based learning aids is a must to improve the teaching and learning process, which can produce more competent and more broad-minded graduates. This research aims to evaluate the Informatics department student's point of view on using audio-visual aids in their English classroom. The result will be useful as one of the considerations in selecting appropriate learning media for the Informatics department in the following semester. The method used is a mixed method, involving one class of the Informatics Engineering department in ITN Malang in the first semester, consisting of 35 students. The research found that even though there are still some limitations on the use of AVA in language classrooms, such as the time required to prepare the material, the degree of difficulty, the lack of teacher guidance, and technical issues, the number of respondents who believe that AVA is applicable outweighs who believe the opposite.